2016
DOI: 10.3389/fendo.2016.00023
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Novel Melanocortin Type 2 Receptor Antagonists on the Corticosterone Response to ACTH in the Neonatal Rat Adrenal Gland In Vivo and In Vitro

Abstract: Stress-induced increases in neonatal corticosterone demonstrate a unique shift from ACTH independence to ACTH dependence between postnatal day 2 (PD2) and day 8 (PD8) in newborn rats. This shift could be due to the binding of a bioactive, non-­immunoreactive plasma ligand to the adrenocortical melanocortin 2 receptor (MC2R) (ACTH receptor). A potent MC2R antagonist would be useful to evaluate this phenomenon in the neonate. Therefore, we investigated the acute corticosterone response to ACTH(1–39) injection in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Many studies have shown that the receptor of ACTH is a G‐protein‐coupled receptor, which may participate in a series of downstream protein phosphorylation events . Thus, the classical phosphorylation of the ERK/STAT3 pathway was examined in VSMCs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies have shown that the receptor of ACTH is a G‐protein‐coupled receptor, which may participate in a series of downstream protein phosphorylation events . Thus, the classical phosphorylation of the ERK/STAT3 pathway was examined in VSMCs.…”
Section: Resultsmentioning
confidence: 99%
“…Many studies have shown that the receptor of ACTH is a G-protein-coupled receptor, which may participate in a series of downstream protein phosphorylation events. 16 Thus, the classical phosphorylation of the ERK/STAT3 pathway was examined in VSMCs. The results showed that when VSMCs were treated with ACTH (1000 nM), ERK phosphorylation was significantly up-regulated after 15 min of treatment, while STAT3 phosphorylation at the Ser727 residue was up-regulated after 30 min ( Figure 2B-D).…”
Section: Acth Regulates Erk and Stat3 Phosphorylation And Promotes mentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study showed that two ACTH analogs, GPS1573 and GPS1574, are potent antagonists of the MC2R in vitro. However, these peptides also had some agonistic and/or antagonistic effects on other melanocortin receptors, and subsequent studies in rats showed disappointing results in vivo (Bouw et al, 2014;Nensey et al, 2016). Further developments might eventually generate a selective MC2R antagonist that could be used as a medical treatment option in dogs with PDH.…”
Section: Melanocortin 2 Receptor Antagonistsmentioning
confidence: 99%
“…They also conducted in vivo experiments in young rats but were unable to show inhibition of the ACTH response even at 400-fold molar excess of antagonist in the case of GPS1573. GPS1574 was partially inhibitory at 30 min after ACTH injection ( 59 ).…”
Section: Approaches To Antagonizing Acthmentioning
confidence: 99%